Modern industrial management as a form of historical development of social management - Prudskiy, Vladimir Grigoryevich; Zhdanov, Maxim Aleksandrovich (Vestnik Permskogo universiteta. Seria Ekonomika = Perm University Herald. Economy, 2016)
Development of engineering and technology accumulates small changes, which when reaching a certain critical mass provide an impetus to the transition to a new technological order. Formation of new technological orders, in its turn, encourages development of the economic sphere. As a result, new industries, forms of management and new business areas appear. This entails development of the processes of separation, cooperation and coordination of social labor and economic activity. Under the influence of these processes, formation of a new system of social labor management takes place, which gives a strong impetus to productivity and efficiency being improved. Since the primitive society, the process of development of social labor management forms has been proceeding in a spiral. In the course of the process, the knowledge accumulated turned into appropriate practical tools and techniques, which were subsequently distributed and improved. With the advent of scientific management, new forms of social labor management have been being prepared by the relevant theoretical research and best practices generalization. These studies form theoretical and methodological bases for the next stage of management science development, and develop the necessary tools, technologies and mechanisms for managing social systems (organizations) under the new historical and economic conditions. Using general scientific methods of research allows us to conclude that we are on the verge of forming a new form of industrial management – postindustrial – which appears to be a specific historical form of social control. At the same time, the organization management system objectively becomes most important intangible asset and a strategic competitive competence of organizations. In view of these circumstances, an idea is put forward that business success in the 21st century will be determined not only by achievements in the development of production technology, but also to a large extent by the level of industrial organization management development, knowledge of regularities and principles of its transformation from the instrumental scheme of the structure control to its most important strategic intellectual resource and a key factor in competitive success. Keywords management, industrial management, post-industrial management, intangible assets, social management, management cycles, industry cycles, technological advances, information economy. References 1. Johnson R., Kast F., Rosenzweig J. Sistemy i rukovodstvo [The theory and management of systems]. Moscow, Sovetskoe radio Publ., 1971. 648 p. 2. Zhdanov M.A. Osobennosti razvitiia upravleniia promyshlennymi proektami kak samostoyatel’noi discipliny menedzhmenta [Features of industrial projects management as an independent management discipline]. Sovershenstvovanie strategicheskogo upravleniia korporatsiiami i regional’naia innovatsionnaia politika. Materialy mezhdunar. nauch.-prakt. konf., Perm’, 6 dek. 2012 [Improving corporate strategic management and regional innovation policy. Proc. of Intern. Sci. and Pract. Conf., Perm, 6 Dec. 2012]. Perm, Perm State University Publ., 2012, pp. 23–28. 3. Zagorodnova E.P. Analiz mezhdunarodnogo opyta primeneniia osnovnykh vidov sistem upravleniia innovatsionnoi deiatel’nost`iu kompanii [Analysis of international experience in applying basic types of systems to manage innovation activities of a company]. Ars administrandi, 2012, no. 2, pp. 35–47. 4. Ivanchenko V.M. Istoricheskie osobennosti stanovleniia i transformatsii gosudarstvennoi sistemy upravleniia [Historical features of formation and transformation of the state management system] Ekonomist [Economist], 2014, no. 6, pp. 3–11. 5. Korenchenko R.A. Obshchaia teoriia organizatsii [General theory of organization]. Moscow, UNITY-DANA Publ., 2003. 286 p. 6. Porter M. Mezhdunarodnaia konkurentsiia: Konkurentnye preimushchestva stran [International competition: The competitive advantage of nations]. Moscow, Mezhdunarodnye otnosheniya Publ., 1993. 896 p. 7. Prudskii V.G. K voprosu o sootnoshenii razvitiia teoretiko-metodologicheskikh osnov i tekhniko-metodicheskogo instrumentariia menedzhmenta [To the question of the relation between the development of theoretical and methodological foundations and technical and methodological tools of management]. Teoriia i praktika korporativnogo menedzhmenta [Theory and practice of corporate management]. Perm, Perm State University Publ., 2011, no. 8, pp. 153–163. 8. Prudskii V.G., Zhdanov M.A. Upravlencheskii proekt kak forma razrabotki, priniatiia i realizatsii innovatsionnogo resheniia [Project management as a form of development, adoption and implementation of innovative decision]. Ars administrandi, 2013, no. 2, pp. 68–78. 9. Prudskii V.G., Oshchepkov V.M. Rol' nematerial'nykh aktivov v regional'nom ekonomicheskom prostranstve [The role of the non-material actives in regional economicy development]. Ekonomika regiona [Ekonomika Regiona (Economy of Region)] Institute of Economics, Ural Division of RAS Publ., 2008, no. 2 (14), pp. 122–126. 10. Strategicheskii menedzhment [Strategic management]. Available at: http://www.lastmanage.ru/ sanvs-518-1.html (accessed 02.12.2015). 11. Trifonov Yu.V., Veretennikov A.A. Dinamicheskaia transformaciia teorii strategicheskogo upravleniia [Dynamic transformation of the theory of strategic management]. Menedzhment v Rossii i za rubezhom [Management in Russia and Abroad], 2014, no. 3, pp. 3–9. 12. Ekonomicheskie tsikly [Economic cycles]. Available at: https://en.wikipedia.org/wiki/Ontogeny (accessed 02.12.2015). 13. Flyvbjerg B. What you should know about megaprojects and why: an overview. Project management journal, 2014, no. 45, pp. 1–15. 14. Freeman C. Technology, progress and the quality of life. Available at: http://www.http://spp.oxfor djournals.org/content/18/6/407.full.pdf+html (accessed 02.12.2015). 15. Laugharn P. The art and science of seizing opportunities. Alliance magazine, 2012, no. 17, pp. 30–33. 16. Sight A. Resource constrained multi-project scheduling with priority rules and analytic hierarchy process. Procedia engineering, 2014, no. 69, pp. 725–734. 17. Stretton A. Series on project success and failure: factors affecting level 1: project management success. PM world journal, 2015, no. 4, pp. 20–35. 18. Teece D.J. Dynamic Capabilities and Strategic Management. Available at: http://www.busine ss.illinois.edu/josephm/BA545_Fall%202013/Teece,%20Pisano%20and%20Shuen%20(1997).pdf (accessed 02.12.2015).